How do production practices and climate change impact the water footprint of dairy farms? - Palhares, Julio Cesar Pascale; De Souza, Debora Pantojo; Carra, Sofia Helena Zanella; Drastig, Katrin (The Science of the total environment, 2025)
Understanding water use in dairy production systems is crucial to promoting production practices and enhancing resilience to climate change. The study aimed to evaluate how production practices and climatic scenarios in different dairy farming systems influence the water footprint of milk production. A total of 67 dairy cattle farms were selected for the study. Climatic scenarios and production practices were proposed as farm-specific interventions targeting three key areas: animal feed, effluent treatment, and nitrogen field application. For all production systems, the combinations exhibiting the highest water efficiency were characterized by the following factors: for green water, a 25 % increase in corn and soybean yields; for blue water, a reduction in milking parlor washing water consumption, an increase of 1 liter of milk per cow per day, and/or a reduction of 1 kilogram in dry matter intake per cow per day; and for grey water, the treatment of effluent from the milking parlor. Conversely, the combinations with the lowest water efficiency were identified as follows: for green water, maize yields decreased by 15 % and soybean yields increased by 12.95 %; for blue water, an increase of 1.5 °C to 2.5 °C in minimum daily temperature and/or a reduction of 1 kilogram in dry matter intake per cow per day; and for grey water, the non-treatment of effluent with the maximum value of α. The findings of this study establish production practices in water scenario analyses concerning water footprints in dairy cattle production systems. [Display omitted] •The study evaluates the water footprint of 67 Brazilian dairy farms.•The production system seems not to influence the WF.•WF can be reduced through the improvement of agricultural and productive practices.•Global warming scenarios increase the values of green and blue water footprints.